(3GdeUHGMs - (3GdNhGQRej GdeWQRj, CHh GdaJM, HQgGf GdOjf, fGUQ Hf YHO GdSjO CHi GdecGQe, J(B610(3g`s ((3efdG SdjeGfs)
(3ChdgG (B:s
(3CeG HYO MeOG ddg Pj GdEfYGe LGA Ydi GdfMh aj GdcdGe cGdedM aj GdWYGeaEf GdhdO GdCYR dG RGd cGSeg eSYhOG hEdi GdNjQ ehOhOG deG GSJXgQ eNJUQ GdEbfGYCQOJ Cf CdNU ef cdGe GdLQLGfj hJQLeJg HcJGH GdeUHGMs
(3BNQgG (B:s
(3dG jLhR hbQjH ef gPg GdEVeGQ Ydi TQjWI GdJaSjQ dCf GdOGd Ydjg daXG CjVG EdG Efg jYbHg haj GdChd eG SHb ef GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 348s
(3eYLe GdeDdajf(B: 4 / 9s
(3cTa GdXfhf(B: 2 / 1708s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs